A Promising Small Molecule for Vanishing White Matter Disease - Divakar S Mithal; Jennifer P Rubin (Pediatric Neurology Briefs Publishers, 2018)
Investigators from Calico Life Sciences LLC and AbbVie report the effects of a novel drug targeting the genetic basis of Vanishing White Matter Disease (VWMD).